Ultrahigh storage density achieved with (1-x)KNN-xBZN ceramics. Issue 8 (July 2020) - Chen, Bi; Tian, Ye; Lu, Jiangbo; Wu, Di; Qiao, Xiaoshuang; Liang, Pengfei; Du, Hongliang; Peng, Zhanhui; Ren, Xiaodan; Chao, Xiaolian; Yang, Zupei
Abstract: A series of (1- x )K0.5 Na0.5 NbO3 - x Ba(Zn1/3 Nb2/3 )O3 ((1- x )KNN- x BZN) nanostructural ceramics was successfully synthesised via solid-state reactions. These nanostructural ceramics exhibited high energy storage density compared with pure KNN ceramics. Further analysis of their dielectric/ferroelectric properties and structures revealed that the addition of BZN alloy disrupted the long-range order of the ferroelectric lattice of pure KNN and favoured the formation of ferroelectric islands and/or polar nano-regions. Consequently, the nanostructured ceramic with x = 0.05 exhibited ultrahigh energy storage density, W, of approximately 9.14 J/cm 3 and recoverable energy storage density, Wrec, of approximately 4.87 J/cm 3 under a fairly low applied electrical field (220 kV/cm). These values exceed the highest values ever reported for KNN-based bulk ceramics. In addition, both excellent fatigue endurance (10 5 cycles) and temperature stability (Δ ε' / ε100°C < 15 % in the range 30–390 °C) were realised with the 0.97KNN-0.03BZN ceramic. Their excellent energy storage properties render KNN-based ceramics potential candidates for application in pulsed-power systems.